Temporal biodiversity change following disturbance varies along an environmental gradient - Kaarlejärvi, Elina; Salemaa, Maija; Tonteri, Tiina; Merilä, Päivi; Laine, Anna‐Liisa (Blackwell Science, 2020)
The diversity and composition of natural communities are rapidly changing due to anthropogenic disturbances. Magnitude of this compositional reorganization varies across the globe, but reasons behind the variation remain largely unknown. Disturbances induce temporal turnover by stimulating species colonizations, causing local extinctions, altering dominance structure, or all of these. We test which of these processes drive temporal community changes, and whether they are constrained by natural environmental gradients. Moreover, we assess to what degree identity shifts translate to changes in dominance structure.
Keywords: forest vegetation; turnover (replacement); boreal zone; beta diversity; clear‐cut; forestry; gains; losses; nitrogen; nutrient balance; richness; succession; temporal turnover; biodiversity